2021
DOI: 10.3390/jof7110898
|View full text |Cite
|
Sign up to set email alerts
|

Novel Botrytis and Cladosporium Species Associated with Flower Diseases of Macadamia in Australia

Abstract: Macadamia (Macadamia integrifolia) is endemic to eastern Australia and produces an edible nut that is widely cultivated in commercial orchards globally. A survey of fungi associated with the grey and green mold symptoms of macadamia flowers found mostly species of Botrytis (Sclerotiniaceae, Leotiomycetes) and Cladosporium (Cladosporiaceae, Dothideomycetes). These isolates included B. cinerea, C. cladosporioides, and unidentified isolates. Amongst the unidentified isolates, one novel species of Botrytis and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
(78 reference statements)
2
17
0
Order By: Relevance
“…Furthermore, the isolates of other fungal genera, Alternaria, Aspergillus, Diaporthe, Epicoccum, Fusarium and Penicillium, did not produce flower blight symptoms on the inoculated racemes. This study showed that multiple species of the genus Neopestalotiopsis, including a previously reported species N. macadamiae (Holtzmann, 1963) and a novel species B. macadamiae (Prasannath et al, 2021a), cause severe grey mould on macadamia inflorescences. Koch's postulates were fulfilled with representative isolates of all these fungi, including the ex-type isolates of the new species previously described by Prasannath et al (2021aPrasannath et al ( , 2021b.…”
Section: Pathogenicity Trialsmentioning
confidence: 56%
See 2 more Smart Citations
“…Furthermore, the isolates of other fungal genera, Alternaria, Aspergillus, Diaporthe, Epicoccum, Fusarium and Penicillium, did not produce flower blight symptoms on the inoculated racemes. This study showed that multiple species of the genus Neopestalotiopsis, including a previously reported species N. macadamiae (Holtzmann, 1963) and a novel species B. macadamiae (Prasannath et al, 2021a), cause severe grey mould on macadamia inflorescences. Koch's postulates were fulfilled with representative isolates of all these fungi, including the ex-type isolates of the new species previously described by Prasannath et al (2021aPrasannath et al ( , 2021b.…”
Section: Pathogenicity Trialsmentioning
confidence: 56%
“…vheenae and N . zakeelii , recently described by Prasannath et al (2021a), that were also proven to be pathogenic on racemes causing dry flower disease in Australia. In this study, P .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, both groups exhibited high prevalence of Malassezia , Cladosporium , Pleosporales, and undifferentiated fungi. While the undifferentiated fungi could be further classified in future studies, Malassezia is associated with a variety of human skin conditions, including dandruff ( Gupta et al, 2004 ), Cladosporium is found in both indoor and outdoor environments and known to be associated with decaying plants and spoiled food ( Bullerman, 2003 ; Prasannath et al, 2021 ), and Pleosporales is responsible for black mold commonly found in indoor environments. Additionally, ordination analysis with background reagents revealed little difference between background and patient sample communities.…”
Section: Discussionmentioning
confidence: 99%
“…The planted area of macadamia in China exceeded 301,206 hm 2 by the end of 2018, and now China has the largest and fastest growing macadamia industry, accounting for over 1/3 of global production acreage ( Shuai et al, 2022 ). Macadamia plants have been reported to be susceptible to a variety of fungal pathogens that can variously infect flower, leaf, fruit, stem, and root tissues ( Akinsanmi and Drenth, 2006 , 2017 ; Akinsanmi et al, 2016a , b ; Prasannath et al, 2021a , b ; Li et al, 2022 ). In this regard, species in the genus Lasiodiplodia represent a serious concern for the crop.…”
Section: Introductionmentioning
confidence: 99%